2000
DOI: 10.1083/jcb.148.5.1075
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Dynamics and Matrix Assembly

Abstract: Fibronectin matrix assembly is a multistep, integrin-dependent process. To investigate the role of integrin dynamics in fibronectin fibrillogenesis, we developed an antibody-chasing technique for simultaneous tracking of two integrin populations by different antibodies. We established that whereas the vitronectin receptor αvβ3 remains within focal contacts, the fibronectin receptor α5β1 translocates from focal contacts into and along extracellular matrix (ECM) contacts. This escalator-like translocation occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
214
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 429 publications
(223 citation statements)
references
References 54 publications
8
214
1
Order By: Relevance
“…[[qv: 25a,40]] The presence of VN integrated in the FN fibrils at the material interface leads to a recovery from this effect, as cells appear to be able to spread (Figure 4E) and reorganize the adsorbed FN (Figure 4C, first column). It has been, in fact, reported that engagement of VN receptors might initiate assembly of FN by cells,7 and this might be in line with our observations. On the other hand, blocking the availability of VN to cells using a monoclonal antibody does not ablate cell response (Figure 4, second column), suggesting that the increased mobility granted by the VN molecules in the FN matrix is sufficient to allow for a better cell attachment and FN reorganization in serum‐free conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[[qv: 25a,40]] The presence of VN integrated in the FN fibrils at the material interface leads to a recovery from this effect, as cells appear to be able to spread (Figure 4E) and reorganize the adsorbed FN (Figure 4C, first column). It has been, in fact, reported that engagement of VN receptors might initiate assembly of FN by cells,7 and this might be in line with our observations. On the other hand, blocking the availability of VN to cells using a monoclonal antibody does not ablate cell response (Figure 4, second column), suggesting that the increased mobility granted by the VN molecules in the FN matrix is sufficient to allow for a better cell attachment and FN reorganization in serum‐free conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Engagement of VN with cell surface receptors contributes to cell adhesion and integrin‐mediated signal transduction. For example, binding of VN to its main integrin receptor (α v β 3 ) was reported to be involved in the initiation of the assembly of FN fibrils by cells 7. The role of adsorbed VN during initial cell–biomaterials interactions has also been addressed in different studies,8 revealing that the protein undergoes dynamic remodeling at the cell–material interface 9.…”
Section: Introductionmentioning
confidence: 99%
“…These fibrillar adhesions contain high levels of tensin and promote cellular mobility but contain low levels of paxillin, vinculin, and tyrosine-phosphorylated proteins. Tensin is a critical component of fibrillary adhesions, and a dominantnegative inhibitor of tensin blocks the formation of this type of extracellular matrix contact (25). It is likely that the formation of fibrillary adhesions is altered in tensin-deficient mice and perhaps contributes to the development of cystic renal disease in these animals (9).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, levels of ␣ 5 ␤ 1 integrin receptors are increased on tubular epithelial cells of patients with nephronophthisis type I (23). Typically, ␣ 5 ␤ 1 integrins translocate away from focal contacts, reorganize the fibronectin molecules of the extracellular matrix, and form fibrillary adhesions along bundles of actin filaments (24,25). These fibrillar adhesions contain high levels of tensin and promote cellular mobility but contain low levels of paxillin, vinculin, and tyrosine-phosphorylated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Upon adhesion to extracellular matrix, cells recruit a highly selective group of membrane and cytoplasmic proteins to the cell-extracellular matrix contact sites, where they connect the extracellular matrix to the actin cytoskeleton and regulate cell shape change, migration, and signal transduction (1)(2)(3)(4)(5)(6). Many mammalian adherent cell types grown in culture form morphologically and molecularly distinct cell-matrix adhesion structures, among which the best characterized are focal adhesions (2, 3) and fibrillar adhesions (or extracellular matrix contacts) (5,(7)(8)(9)(10)(11). Focal adhesions represent firm substrate attachment sites that typically are arrowheadshaped and contain clusters of integrins and cytoskeletal and signaling molecules including talin, viculin, focal adhesion kinase, and paxillin.…”
mentioning
confidence: 99%